2020
DOI: 10.1186/s13102-020-00174-z
|View full text |Cite
|
Sign up to set email alerts
|

Force production during the sustained phase of Rugby scrums: a systematic literature review

Abstract: Background: Since World Rugby changed the laws regarding scrums in the 2013-2014 season, the sustained push phase of the scrum has increased in tactical importance. Therefore, the purpose of this systematic literature review was to examine the biomechanical demands during the sustained push phase of individual, unit, and full pack scrummaging. Methods: Pubmed, EBSCO (specifically and simultaneously searching Academic Search Premier, CINAHL, and SPORTDiscus), and Google Scholar were searched for any research th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…The angle of the knee joint at the time of scrum push is 130°-155°. A study using 14 cadaver knees has shown that at 150°knee flexion, the contact pressure is the highest near the middle segment of the lateral meniscus (24,25). These findings support the deterioration and injury of the middle segment of the lateral meniscus by the repeated push maneuvers during the scrum.…”
Section: Discussionmentioning
confidence: 73%
“…The angle of the knee joint at the time of scrum push is 130°-155°. A study using 14 cadaver knees has shown that at 150°knee flexion, the contact pressure is the highest near the middle segment of the lateral meniscus (24,25). These findings support the deterioration and injury of the middle segment of the lateral meniscus by the repeated push maneuvers during the scrum.…”
Section: Discussionmentioning
confidence: 73%
“…First, very little data exist for female rugby players. These players represent a significant proportion of the overall player base, yet there are few studies that have evaluated female players in any capacity [ 51 ], let alone using the IMTP. In addition, it is clear that the majority of data has been collected in Europe; few data have been collected in other areas of the world in which rugby is both popular and is played at a high level.…”
Section: Discussionmentioning
confidence: 99%
“…During prebind, the front-row players are required to bind opposing players with the head facing the opposing players' shoulders and hip and knee angles at 120°( more vertical position). The prebind position reduces the distance between packs, the speed at impact, and the risk of head-to-head contact 108,109 . Following the scrum rule changes and educational efforts, a marked reduction of catastrophic cervical spine injuries (1.8 to 1.0/100,000 from 2006 to 2013 110 ) was reported [110][111][112][113][114] .…”
Section: Rugbymentioning
confidence: 99%